Pengaruh Model Pembelajaran Kooperatif Tipe Tgt Terhadap Hasil Belajar Siswa Kelas IV Mata Pelajaran IPAS di SD - Chornelia P.H Pasaribu; Bogor Lumban Raja; Anton Sitepu; Darinda Sofia Tanjung; Dyan Wulan Sari HS (Departement of Mathematics Education, 2024)
The research applies the TGT learning model. The TGT learning model is directed towards a group learning model, which applies students working together with each other in a group led by one of the students, who is able to take responsibility in the group. This research uses a quantitative research approach. The population of this research are all class IV students SD Negeri 064023 Medan Tuntungan with a total of 25 students. Non-probability sampling was taken using samples and a sample of 25 students was obtained. The results of the research show that student learning outcomes using the TGT type learning model are in the good category with an average of 82.72. Results correlation coefficient (r_xy) or r_count = 0.623 with a significance level of 5% with the number of respondents (n) = 25 students so that r_table = 0.396. From the results of these calculations it shows that 0.623 ≥ 0.396 with student learning outcomes which has a strong relationship, it can be It was concluded that there was an influence between the TGT learning model on the learning outcomes of fourth grade students at SD Negeri 064023 Medan Tuntungan. Based on the results of the hypothesis test (t-test) with a value of t_count ≥ t_table, namely 3.824 ≥ 1.708 at a significance level of 0.000 < 0.05. These data can shows that Ha is accepted, namely that there is an influence between the TGT type cooperative learning model (X) and student learning outcomes (Y).